Influência do amortecimento via circuitos elétricos shunt sobre o comportamento dinâmico e aeroelástico de painéis planos - Leão, Leandro de Souza (2015)
Dynamic and aeroelastic stabilities of aeronautical structures have a fundamental importance in engineering design. One must know, a priori, the answers for being expected from these systems, so that they are able to perform their tasks with success, reliability and safety. With increasing engineering challenges, weight reduction and smaller level of vibrations, without loss of efficiency, represent an inexhaustible source of work and research. For this purpose, composite structures, which combine more than one material in order to obtain a new one, figure as an excellent alternative, because they are lighter and possess better mechanical properties. It is known that light structures tend to be flexible, which may lead to static and dynamic instabilities. In order to avoid or suppress these instabilities there is clear need of proposing engineering solutions to design structures with the ability of dissipating energy and stabilizing itself when subjected to external perturbations, particularly in the aerospace sector, where efficiency at low weight is crucial. In this sense, smart structures, are presented as an excellent alternative, being able to stabilize satisfactorily these new structures. This master\'s work aims at proposing smart aircraft structures, such as panels and wing typical sections, which are able to combine low weight, good mechanical properties, besides presenting enhanced dynamic and aeroelastic behaviors, without requiring external power source of energy to carry out their control. So that, this research proposes the use of multimodal electrical resonant shunt circuits, combined in series topology with the piezoelectric patch. This represents a passive form of control and has the advantages of being very simple, reliable with low cost.